The Effect of Supportive Therapy in Reducing Anxiety in Juvenile Inmates in Class IIb Correctional Institutions, Purwakarta Regency, Indonesia - Pratiwi, Shinny Ria (Archives of The Medicine and Case Reports, 2024)
Anxiety is a mental health problem that is often experienced by teenagers, including juvenile inmates. Supportive therapy is one intervention that can be used to reduce anxiety in adolescents. This study aims to determine the effect of supportive therapy on reducing anxiety in juvenile inmates at the Class IIb Correctional Institution, Purwakarta Regency, Indonesia. This research uses a quasi-experimental design with a pretest-posttest control group design. The research sample consisted of 30 juvenile inmates who were divided into two groups, namely the intervention group (15 people) and the control group (15 people). The intervention group was given supportive therapy for 4 weeks, while the control group was given no intervention. The results of the study showed that there was a significant reduction in anxiety in the intervention group after being given supportive therapy. The average level of anxiety in the intervention group before the intervention was 2.67 (SD=0.488), while after the intervention, it was 1.53 (SD=0.516). This difference is statistically significant (p<0.001). Based on the results of this research, it can be concluded that supportive therapy can reduce anxiety in juvenile inmates. Supportive therapy can help juvenile inmates understand and address the causes of their anxiety, as well as increase their ability to use adaptive coping resources.